Predictors of Intent to Pursue a College Health Science Education among High Achieving Minority 10th Graders - Katarzyna A. Zebrak; Daisy Le; Bradley O. Boekeloo; Min Qi Wang (Arizona State University, 2013)
Minority populations are underrepresented in fields of science, perhaps limiting scientific perspectives.  Informed by recent studies using social cognitive career theory, this study examined whether three conceptual constructs: self-efficacy, perceived adult support, and perceived barriers, along with several discrete and immutable variables, were associated with intent to pursue college health science education in a sample (N = 134) of minority youth (67.2% African American).  A paper-and-pencil survey about pursuit of college health science was administered to 10th graders with a B- or better grade point average from six high schools in an underserved community.  Results indicated that the three conceptual constructs were bivariate correlates of intent to pursue college health science.  Only perceived adult support and knowing whether a parent received college education were significant predictors in a multiple regression model.  These results build on previous research and provide further insight into youth decision-making regarding pursuit of college health science.